Uncontrolled Epistaxis Secondary to Traumatic Pseudoaneurysm of the Maxillary Artery. (6th December 2011) - Adil, Eelam; Setabutr, Dhave; Carr, Michele M.
Abstract : We describe a rare case of traumatic pseudoaneurysm of the maxillary artery following a fall. The patient presented with epistaxis that could not be controlled with anterior and posterior nasal packing. She was urgently taken to the angiography suite for evaluation and ultimately underwent embolization of a left maxillary artery pseudoaneurysm with 500–700 micron Contour PVA followed by coiling with two 3 mm Tornado coils. Bleeding subsided after embolization, and the patient suffered no neurologic sequelae.